Pemberdayaan Perempuan dalam Pembuatan Pola Dasar Busana untuk Meningkatkan Pendapatan Keluarga di Kabupaten Pangkep - Marhawati Marhawati; Agus Syam; Nurdiana Nurdiana (Universitas Negeri Makassar, 2018)
The aim of this Community Partnership Program is to empower women, especially housewives. Weprovide training of a practical basic clothing pattern. It is expected that with this skill, the women in Pangkajenedistrict of Pangkep regency will be able to turn it into business to improve their prosperity. The activities in thistraining are (a) providing theories on how to take measures, (b) how to make basic patterns of clothing with a ¼scale, (c) how to make basic pattern with the actual size, (d) how to make a basic pattern for body, skirt and arm, (d)demo session on taking a measure, make basic pattern with the actual scale and size, and make a basic pattern ofbody, skirt and arm. The result of this training shows that the participants understand in making basic clothingpatterns and make their own clothes or turn it as a side job to increase their family income.